Different Surgical Approaches for Early-Stage Ovarian Cancer Staging. A Large Monocentric Experience - Cianci, Stefano; Capozzi, Vito Andrea; Rosati, Andrea; Rumolo, Valerio; Corrado, Giacomo; Uccella, Stefano; Gueli Alletti, Salvatore; Riccò, Matteo; Fagotti, Anna; Scambia, Giovanni; Cosentino, Francesco (Frontiers in Medicine, 2022)
Introduction Ovarian cancer is the third most frequent gynecological cancer. In early stage ovarian cancer (ESOC) comprehensive surgical staging is recommended. Surgical staging is traditionally approached by laparotomy, although minimally invasive surgery can be a valid alternative in selected patients. This study aims to analyze the surgical and oncological outcomes of three different surgical approaches in a large series of patients. Methods We retrospectively included all histologically proven ESOC cases treated between January 2014 and December 2017. ESOC was defined as stage IA to IIB according to the 2018 FIGO staging system. Subjects were divided into groups 1, 2, and 3, based on the surgical approach (open abdominal, laparoscopic, or robotic, respectively). Results Within patients enrolled during the study period, 455 met the inclusion criteria. No difference in intraoperative complications was recorded in the three groups (p = 0.709). Conversely, a significant difference occurred in postoperative complications (16.2 vs. 3.8 vs. 11.1%, in groups 1, 2, and 3 respectively, p = 0.004). No difference was found in overall survival (OS) (32 vs. 31 vs. 25 months, p = 0.481) and disease-free survival (DFS) (26 vs. 29 vs. 24 months, p = 0.178) in groups 1, 2, and 3, respectively. At univariate analysis FIGO stage I (p = 0.004) showed a lower recurrence rate compared to FIGO stage II. Conclusion No significant difference was found in OS and DFS among the three groups (open, laparoscopic, and robotic). The minimally invasive approach showed lower rate of complications than the laparotomic approach.